The Impact of an Ice Slurry-Induced Gastrointestinal Heat Sink on Gastrointestinal and Rectal Temperatures Following Exercise - Thomas A. Deshayes; Adrien De La Flore; Jonathan Gosselin; Jeff Beliveau; David Jeker; Eric D.B. Goulet (MDPI AG, 2019)
Gastrointestinal temperature (Tgint) measurement with a telemetric pill (TP) is increasingly used in exercise science. Contact of cool water with a TP invalidates Tgint assessment. However, what effect a heat sink created in the proximity of a TP may have on the assessment of Tgint remains unknown. We examined the impact of an ice slurry-induced heat sink on Tgint and rectal temperature (Trec) following exercise. After 20 min of seating (20−22 °C, 25−40% relative humidity (RH)), 11 men completed two intersperse exercise periods (31−32 °C, 35% RH) at 75−80% of estimated maximal heart rate until a Trec increase of 1 °C above baseline level. Following the first exercise period, participants were seated for 45 min and ingested 7.5 g·kg−1 of thermoneutral water, whereas, following the second period, they ingested 7.5 g·kg−1 of ice slurry. Both Tgint and Trec were measured continuously. The TPs were swallowed 10 h prior to the experiments. A bias ≤0.27 °C was taken as an indication that Tgint and Trec provided similar core temperature indices. Mean biases and 95% limits of agreement during passive sitting, first exercise, water ingestion, second exercise, and ice slurry ingestion periods were 0.16 ± 0.53, 0.13 ± 0.41, 0.21 ± 0.70, 0.17 ± 0.50, and 0.18 ± 0.66 °C, respectively. The rates of decrease in Tgint and Trec did not differ between the water and ice slurry ingestion periods. Our results indicate that ice slurry ingestion following exercise does not impact TP-derived assessment of Tgint compared with Trec.